Millennial dissonance: an analysis of the privacy generational gap - Sher, Matthew J. (2012)
The young Millennial generation has adopted social media and internet technology to an unprecedented degree. But this generation’s extensive usage of online services leaves Millennials open to various privacy vulnerabilities that have emerged with the new technology. Older generations hold concern that Millennials are ignoring the value of privacy when disclosing their personal information in exchange for online connectivity. This paper investigates the generational privacy concern through different perspectives. It cites studies of Millennial behavior to ascertain the generation’s outlook on privacy. It extrapolates from recent online privacy trends to outline possible consequences of Millennial privacy behaviors. It concludes with some reasons the Millennial generation may effectively resist exploitation by invasive database corporations.